Innovation of flexifold table - Zainurin, Siti NurNadiera; Arfizal, Nur Ain Syuhada; Mohd Arshad, Ainin Sofiya; Azman, Dinnie Asyraf (2024)
This paper presents the innovation of a foldable USB table, designed to offer a portable workspace solution catering to the growing demand for flexibility and convenience in modern work environments. The innovation addresses the inherent limitations of conventional tables by integrating foldable functionality and USB connectivity into a compact design. The problem statement revolved around the need for versatile workspaces that could adapt to varying work scenarios and spatial constraints. The objectives of this innovation were to enhance portability, usability, and connectivity while maintaining ergonomic design principles. The methodology involved iterative prototyping, user feedback incorporation, and performance evaluation. Findings indicate that the foldable USB table meets the desired criteria for portability, stability, and connectivity, facilitating efficient work setups in diverse settings. The conclusion underscores the significance of such innovations in fostering productivity and comfort for users. Commercial potential lies in catering to the burgeoning market of remote workers, students, and professionals seeking portable workspace solutions, thereby offering a competitive edge in the furniture industry.